Politische und ökonomische Steuerungsfaktoren der Bildung eines Verdichtungsraumes am Beispiel der Randstad Holland - Borchert, J.G. (ERDKUNDE, 1980)
In their endeavours to explain spatial reality, geographers have so far largely limited themselves to the study of the behaviour of socio-spatial units of activity in the sense of classical location theories. Theoretical reasons lead to the acknowledgement of the necessity to recognise external effects and political factors, particularly in agglomeration areas. The example of suburbanisation in the Randstad area illustrates the significance of the factors. Only if it is known how regionally effective decisions are arrived at can the discrepancy be understood between the ideal - however it may be formulated - and reality in planning areas. It has become evident that man has paradoxically created an environment for himself which he does not desire.